Session Topic: Money and Capital Markets: Discussion - Mandell, Lewis; Black, Harold; c. Aspinwall, Richard (Journal of Finance, 1977)
Lewis Mandell, Harold Black, Richard c. Aspinwall, Session Topic: Money and Capital Markets: Discussion, The Journal of Finance, Vol. 32, No. 2, Papers and Proceedings of the Thirty-Fifth Annual Meeting of the American Finance Association, Atlantic City, New Jersey, September 16-18, 1976 (May, 1977), pp. 588-592